2014
DOI: 10.1208/s12249-014-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1

Abstract: Ginsenoside Rb1 (Rb1) is the most predominant ginsenoside isolated from the roots of ginseng (Panax ginseng C. A. Meyer). This compound is active in various human biological pathways that are involved in human collagen synthesis and inhibition of cell apoptosis. In this study, the skin-whitening effects of Rb1 were investigated in B16 melanoma cells. Our results showed that Rb1 inhibited melanogenesis in α-melanocyte-stimulating hormone (α-MSH)-stimulated B16 cells in a dose-dependent manner, which collectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Meyer [8]. Rb1 has received much attention due to its biological functions, especially the various neuroprotective effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meyer [8]. Rb1 has received much attention due to its biological functions, especially the various neuroprotective effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several reports shown that the anti-melanogenic effect of ginsenoside. 19,20) Our result showed that the strong mushroom tyrosinase inhibitory activity (IC 50 =9.8 µM) with picrionoside A. However, tyrosinase activity in the melan-a cell showed the weak inhibition rate.…”
Section: Physical Properties and Nmr Data Of Picrionosidementioning
confidence: 70%
“…Ginsenoside F1, a derivative of ginsenoside Rg1, has been found to be effective as skin whitening agent by suppressing tyrosinase (Yoo et al, 2011). In vitro studies of ginsenoside Rb1, an aglycone of ginsenoside Rh4, and ethanol extract of ginseng seed have also been shown to have skin whitening effect though inhibition of tyrosinase activity and melanin content (Lim et al, 1999;Jeong et al, 2013;Wang et al, 2014). However, no study has been made to evaluate the antimelanogenic activities of aqueous CRMG extract and ginsenoside Re.…”
Section: Introductionmentioning
confidence: 99%